Microwave Bandpass Filter Integrated with Notch Response for Wide-band Applications - Mussa Mabrok; Zahriladha Zakaria; Nurhana Abu Hussin; Mohamad Ariffin Mutalib (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper presents the design of wide-band bandpass filter using microstrip structure at 3-6GHz with fractional bandwidth of 66.67% based upon short-circuited stubs structure of 5th degree. In order to avoid the interference from existing system that operates in the frequency band, the folded stepped impedance resonator (SIR) was introduced to generate a narrow notch band at 5.2GHz. Pin diode is employ as switching mechanism for the notch response. This design is simulated by Advance Design System (ADS) software and using Roger Duroid 4350B with a dielectric constant of 3.48, substrate thickness 0.508mm and loss tangent 0.0019.The achieved return loss is better than 15dB and insertion loss is less than 1dB.The designed filter can be used in microwave communication systems such as wireless communication devices and military applications (radar system).